Electron tunneling in a multibarrier potential - Korostil, A.; Korostil, Yu. (Моделювання та інформаційні технології, 2009)
The electron and spin transport in nanoscopical heterostructures taking is
considered taking into account features of electron spectra. It is shown efficiency of
effective mass methods for an quantum-mechanical description of electron tunneling
through potential barriers of the system. It is shown the description of coherent
electron transport in multibarrier electron potentials.